Comparative study of abdominal hysterectomy and vaginal hysterectomy in non-descent cases a prospective study - Mehta, Kalpana; Prakash, Om; Fatehpuriya, Dharmendra Singh; Verma, Leena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In the present times, the emphasis on minimally invasive surgery has lead to a resurgence of interest and importance of VH for non-prolapsed indications i.e. non-decent vaginal hysterectomy (NDVH) as the scar less hysterectomy. It has several benefits over abdominal hysterectomy in terms of cosmetic advantages, lesser post-operative morbidity and faster recovery. The objectives of the study was to compare and assess various factors like operative duration of surgery, intra operative blood loss, intra operative and post-operative complications, post-operative analgesia requirement, post-operative ambulation and duration of post-operative hospital stay and to put forward best route of hysterectomy. Methods: Hundred cases fulfilling, the selection criteria were included in the study. Patients were randomly divided in two groups-NDVH (non-decent vaginal hysterectomy) and abdominal hysterectomy. Results: Operative time, intra operative blood loss and post-operative morbidity was less in NDVH groups. Conclusions: Non-decent vaginal hysterectomy is a better alternative to abdominal hysterectomy in cases with benign pathology of the uterus, uterine size <14 weeks, uterus with good mobility and adequate vaginal access.